2012
DOI: 10.1016/j.transproceed.2012.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Calcineurin Inhibitors to Everolimus With Low-Dose Cyclosporine in Renal Transplant Recipients With Squamous Cell Carcinoma of the Skin

Abstract: Squamous cell carcinoma of the skin (SCC) is the most frequent cancer in renal transplant recipients. Conversion to mammalian target of rapamycin inhibitors after diagnosis of SCC may reduce the incidence of recurrence of skin cancer. This retrospective study evaluated the outcome of renal transplant recipients followed by the Renal Unit with posttransplant diagnosis of SCC treated with conversion from calcineurin inhibitors (CNIs) to Everolimus (EVR) associated with low-dose cyclosporine. Eleven patients deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The evidence relating to switch to sirolimus following diagnosis of NMSC is more extensive than for everolimus [64], but data is accumulating regarding intervention with everolimus. Caroti et al have described a series of eleven kidney transplant patients who developed SCC at a median of 107 months after transplant [65]. The lesions were surgically excised and patients were switched to everolimus with low-dose cyclosporine (CsA).…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…The evidence relating to switch to sirolimus following diagnosis of NMSC is more extensive than for everolimus [64], but data is accumulating regarding intervention with everolimus. Caroti et al have described a series of eleven kidney transplant patients who developed SCC at a median of 107 months after transplant [65]. The lesions were surgically excised and patients were switched to everolimus with low-dose cyclosporine (CsA).…”
Section: Kidney Transplantationmentioning
confidence: 99%
“…As seen in studies of pre-emptive conversion to everolimus, a shorter time post-transplant was associated with greater renal benefit [52] and patients with very poor baseline renal function tended to progress to end-stage renal disease [48].…”
Section: Everolimus As Rescue Therapymentioning
confidence: 92%
“…The literature includes a number of single-center reports from small series of maintenance kidney transplant patients who were switched from CNI therapy to everolimus in response to declining renal function [45,46], malignant neoplasms or nonmelanoma skin cancer [47][48][49][50] or, more frequently, a mixture of indications but primarily renal deterioration or malignancy [51][52][53][54]. Studies of cohorts switched due to renal causes or for mixed reasons have consistently shown a significant improvement in renal function over follow-up periods ranging from six months to two years [45,46,[51][52][53][54].…”
Section: Everolimus As Rescue Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, at one yr, conversion to sirolimus was associated with a significant risk reduction both in all patients and those with only a single previous SCC (Table ). While randomized data are not yet available for everolimus, a low recurrence rate (two of 11 patients) was reported in a retrospective study of kidney transplant recipients who were converted to everolimus plus low‐dose cyclosporine after developing SCC of the skin in the post‐transplant period .…”
Section: Current Roles For Mtor Inhibitors In Immunosuppressive Theramentioning
confidence: 99%